Improving the Economic Legal Framework for Autonomy of Public Universities in Vietnam: Perspectives, Strategic Orientations, and Policy Solutions - Cu, Nguyen Van (VNU Journal of Science: Legal Studies; Vol 41 No 2, 2025)
University autonomy has become an inevitable trend in the reform of higher education in Vietnam, with financial autonomy playing a crucial role in determining the operational effectiveness and sustainable development of public universities. This article focuses on analyzing key theoretical perspectives on economic autonomy in higher education, emphasizing the essential relationship between autonomy, accountability, and financial transparency. Employing an integrated methodological approach, including policy analysis, legal document review, and case studies of selected public universities, the article identifies existing limitations and shortcomings in the current legal framework governing financial autonomy. Based on this analysis, it proposes strategic directions to expand financial self-governance in higher education institutions. Specifically, it advocates for the delegation of authority to manage and utilize institutional assets, coupled with the establishment of appropriate supervisory mechanisms to ensure the effective and responsible use of public resources. Accordingly, the article presents critical recommendations for developing and improving the legal framework on university autonomy, including amendments to the Law on Higher Education, the establishment of mechanisms to mobilize and allocate financial resources, and enhancements to financial oversight systems in the context of institutional autonomy. These proposals aim to promote a more substantive, effective, and equitable implementation of university autonomy in Vietnam.